ASPEK SOSIAL DALAM GADAI - Agus Salim NST (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Pawn classical jurists expressed only personal. This means that debts that only occurs between a person in need and someone who has excess property. In the current era, in accordance with the development and economic progress, the lien applies not only between private, but also between private financial institutions, such asbanks. In the current era, in accordance with the development and economic progress, the lien applies not only between private, but also between private financial institutions, such as banks. To obtain credit from financial institutions, banks are also demanding collateral items that can be held by the bank as collateral for a loan.